THE EFFECT OF APPLICATION OF BLOCKCHAIN TECHNOLOGY ON DIGITAL MARKETING - Jeremy Iron Wiratama; Lamhot Henry Pasaribu (Enrichment : Journal of Management, 2021)
This study aims to analyze 1) Does blockchain have a positive and significant effect on the use of big data?, 2) Does big data have a positive and significant effect on digital marketing?, 3) Does blockchain have a positive and significant effect on the future of digital marketing? This study uses survey method, and in data collection, online questionnaires were used and distributed to people who understand about the concept of blockchain technology and digital marketing. The sampling method of this research is purposive sampling with the number of samples is 118 people. The approach used is Partial Least Square-Structural Equation Modelling, using the Smart PLS 3.0 Program. The results showed that 1) Blockchain has a positive and significant effect on big data, 2) Big data has a positive and significant effect on digital marketing, 3) Blockhain has a positive and significant effect on digital marketing.